PENGARUH BESARNYA VOLUME PEMBIAYAAN OLEH LEMBAGA KEUANGAN MIKRO (KSP) TERHADAP PENINGKATAN VOLUME USAHA PETERNAK AYAM PETELUR DI DESA SURUHWADANG KECAMATAN KADEMANGAN KABUPATEN BLITAR - NUR FAUZIAH (Universitas Negeri Surabaya, 2014)
The purpose of this research is to determine the extent of the influence of the large volume of financing by microfinance institutions (Credit Unions) against the increase in business volume breeder laying hens in the Suruhwadang-Kademangan Blitar. This type of research is descriptive quantitative analysis, using simple linear regression. Hypothesis test results obtained financing for the volume variable significance value of 0.0000 at α = 5 %. This means that the hypothesis that